1998
DOI: 10.1093/intqhc/10.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Understanding physicians' imaging test use in low back pain care: the role of focus groups

Abstract: Our findings suggest that gaining information from focus groups prior to designing physician behavior change interventions may aid the design of more effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 34 publications
0
58
0
2
Order By: Relevance
“…The perceived failure of general/family practitioners to take individual's concerns seriously and to provide sufficient time to understand their problem is a recurrent theme in previous studies (25)(26)(27). However, the strength of participants' overall negative feelings about the diagnosis and advice they have received is quite surprising because it is far beyond that identified in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived failure of general/family practitioners to take individual's concerns seriously and to provide sufficient time to understand their problem is a recurrent theme in previous studies (25)(26)(27). However, the strength of participants' overall negative feelings about the diagnosis and advice they have received is quite surprising because it is far beyond that identified in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…From a diagnostic perspective, tests are ordered to modify the pretest probability of disease [15,29,30,32,33,36],to rule in or rule out disease, or to refer for further evaluation [1,15,29,32,33]. In primary care tests are more commonly used to rule out a condition or to help the doctor to make a decision about referral, or provide further information on the patient to a secondary care specialist [5,20,32].…”
Section: Diagnostic Factorsmentioning
confidence: 99%
“…However, the results of two studies addressing this issue were contradictory: one found that younger doctors and male doctors tended to order fewer tests [6], whereas the other found that older doctors ordered fewer [26]. Both time pressures [5,30,36] and fear of litigation [5,27,30,37] have been found to result in increased testing. Individual doctors respond differently to patients' requests for unnecessary tests [5,13,17].…”
Section: Doctor-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may order imaging for low back pain to appear to be "doing something," or from fear of litigation. [16][17][18][19][20][21] Health system-level factors that may influence these physician behaviors include local practice customs; incentives to follow guidelines (or, conversely, to provide care that patients request); time restraints; and access to automated reminders in the EHR, counseling materials, and radiology services. [19][20][21] The purpose of these analyses was to generate hypotheses for further exploration and development of interventions.…”
Section: Introductionmentioning
confidence: 99%